Linseed components are more effective than whole linseed in reversing diet-induced metabolic syndrome in rats - Shafie, Siti Raihanah; Wanyonyi, Stephen; Panchal, Sunil K.; Brown, Lindsay (MDPI, 2019)
Linseed is a dietary source of plant-based ω–3 fatty acids along with fiber as well as lignans including secoisolariciresinol diglucoside (SDG). We investigated the reversal of signs of metabolic syndrome following addition of whole linseed (5%), defatted linseed (3%), or SDG (0.03%) to either a high-carbohydrate, high-fat or corn starch diet for rats for the final eight weeks of a 16–week protocol. All interventions reduced plasma insulin, systolic blood pressure, inflammatory cell infiltration in heart, ventricular collagen deposition, and diastolic stiffness but had no effect on plasma total cholesterol, nonesterified fatty acids, or triglycerides. Whole linseed did not change the body weight or abdominal fat in obese rats while SDG and defatted linseed decreased abdominal fat and defatted linseed increased lean mass. Defatted linseed and SDG, but not whole linseed, improved heart and liver structure, decreased fat vacuoles in liver, and decreased plasma leptin concentrations. These results show that the individual components of linseed produce greater potential therapeutic responses in rats with metabolic syndrome than whole linseed. We suggest that the reduced responses indicate reduced oral bioavailability of the whole seeds compared to the components.